Dataset of material measurement based on SEM images of Ag/TiO(2) nanocomposite material synthesized via Horizontal Vapor Phase Growth (HVPG) technique - Muflikhun, Muhammad Akhsin (Data Brief, 2020)
This data describes about the measurement technique of Ag/TiO(2) nanocomposite materials that successfully synthesized via Horizontal Vapor Phase Growth (HVPG) technique. The data are obtained after specimens were placed in the Scanning Electron Microscope (SEM) chamber to be analyzed. The present data were captured from SEM with different magnification. There are total 27 variable data to be analyzed from three different parameters; growth temperature, baking time and zones. In total, 9 different quartz tubes that contains of Ag/TiO(2) nanocomposite material are evaluated. Data are described in average value where the different calculations are presented. Raw data are also embedded in the Appendix for further analysis purposes. These data can be useful as the information of size measurement of Ag/TiO(2) nanocomposite materials in different temperature and time during synthesis process.